Impacts of Land Use on Water and Sediment Quality of Sampadi River, Malaysia - Ling, Teck Yee; Eklip, Mildred; Bimol, Mordi; Lee, Nyanti (IDOSI Publication, 2011)
Aquaculture is an important industry in Malaysia due to water availability. Recent commercial crop development in the Sampadi River watershed may have an impact on the water quality of the river. Therefore a study was conducted to determine the water and sediment status of selected stations along that river. Results showed that oxygen demand, nitrogen and phosphorus in the water at all stations were higher at low tide than at high tide except reactive phosphorus at the station near shrimp culture. The station near oil palm plantation showed the lowest pH and DO, the highest TKN and RP and the second highest in COD in the water and the highest in TOC, TKN and TP in the sediment. The station near shrimp farming showed the highest COD, second highest TKN and the highest high tide water reactive phosphorus. In addition, sediment copper and TKN was the highest and second highest among the stations. The station that was near the residential area was the highest in low tide reactive phosphorus and the second highest in BODs, the highest in sediment lead and cadmium.